1986
DOI: 10.1007/bf02577940
|View full text |Cite
|
Sign up to set email alerts
|

Embolization of the left gastric artery in the absence of angiographic extravasation

Abstract: Nine high-risk patients with endoscopic evidence of bleeding from the left gastric artery territory without angiographic extravasation were embolized to prevent rebleeding. Three were embolized with Gelfoam particles, 1 with Gianturco coils, and 5 with Gelfoam plus coils. Three patients rebled; 2 were embolized with Gelfoam only, and the third with coils only. No rebleeding occurred in the 5 patients treated with Gelfoam plus coils. No ischemic complications occurred. We conclude that embolization of the left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Gunderman et al had an overall positive scintigraphic screening in 46% of the 249 patients undergoing 99mTc-RBC scans over a 10-year study period [30]. Similar positive scintigraphic screening rates ranging from 46-73% have been confirmed [31,[66][67][68]. Jacobson and Cerqueira showed that upper sources of bleeding in the stomach or small bowel were more common when the nuclear screening studies became positive on delayed imaging [31].…”
Section: Intermittent Gi Bleed/empiric Embolizationmentioning
confidence: 70%
See 2 more Smart Citations
“…Gunderman et al had an overall positive scintigraphic screening in 46% of the 249 patients undergoing 99mTc-RBC scans over a 10-year study period [30]. Similar positive scintigraphic screening rates ranging from 46-73% have been confirmed [31,[66][67][68]. Jacobson and Cerqueira showed that upper sources of bleeding in the stomach or small bowel were more common when the nuclear screening studies became positive on delayed imaging [31].…”
Section: Intermittent Gi Bleed/empiric Embolizationmentioning
confidence: 70%
“…Because of the safety of the procedure, they recommended empiric embolization of the upper GI tract for acute bleeding when guided by endoscopic findings [35]. Success with empirical treatment substantiates its continued use [33,[68][69][70][71].…”
Section: Intermittent Gi Bleed/empiric Embolizationmentioning
confidence: 95%
See 1 more Smart Citation
“…12 The efficacy of blind embolization, defined as embolization without angiographic proof of extravasation, is controversial. 30 Dempsey et al 10 concluded that blind embolization was not helpful in controlling gastrointestinal hemorrhage, but Morris et al 31 found that the blind embolization of the left gastric artery was effective in preventing rebleeding when an active bleeding site had been demonstrated by endoscopy. In our study, blind embolization was performed in 5 arteries of 4 patients when an active bleeding site had been demonstrated by endoscopy or scintigraphy or was suspicious on angiogram.…”
Section: Discussionmentioning
confidence: 97%
“…In lower-GI-bleeding, reported mortality rates after a negative arteriographic study might range from 0 to 17% [12,16,19,20]. In upper-GI-bleeding, studies reporting outcome of patients with a negative arteriography are rare and inconsistent [21,22].…”
mentioning
confidence: 97%